2015
DOI: 10.1186/s40959-015-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac safety of afatinib: a review of data from clinical trials

Abstract: Background: Afatinib is an oral irreversible ErbB family blocker that targets epidermal growth factor receptor (EGFR/ErbB1), human epidermal growth factor receptor 2 (HER2/ErbB2), and HER4 (ErbB4) and is approved for the first-line treatment of advanced non-small cell lung cancer (NSCLC) with certain sensitizing EGFR mutations. As anti-HER2 therapies have been associated with cardiac dysfunction, we report cardiac safety data for afatinib. Methods: Cardiac data were analyzed from phase III trials of afatinib 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“… 16 , 20 However, there is inconclusive evidence or no clear association for an effect on LVEF with other HER2-targeting therapies, such as lapatinib, sunitinib, and afatinib. 16 , 21 - 24 Similar to the osimertinib data presented here, an analysis of cardiac failure with afatinib, a treatment for patients with EGFRm metastatic NSCLC, reported low rates of protocol-defined cardiac failure and clinically significant LVEF reductions, comparable to those seen with the control treatment arms. The authors concluded that afatinib was not associated with cardiac failure or clinically significant LVEF reductions in the clinical trial program; therefore, no evidence of direct or primary cardiac or cardiovascular toxicity was found.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“… 16 , 20 However, there is inconclusive evidence or no clear association for an effect on LVEF with other HER2-targeting therapies, such as lapatinib, sunitinib, and afatinib. 16 , 21 - 24 Similar to the osimertinib data presented here, an analysis of cardiac failure with afatinib, a treatment for patients with EGFRm metastatic NSCLC, reported low rates of protocol-defined cardiac failure and clinically significant LVEF reductions, comparable to those seen with the control treatment arms. The authors concluded that afatinib was not associated with cardiac failure or clinically significant LVEF reductions in the clinical trial program; therefore, no evidence of direct or primary cardiac or cardiovascular toxicity was found.…”
Section: Discussionsupporting
confidence: 62%
“…The authors concluded that afatinib was not associated with cardiac failure or clinically significant LVEF reductions in the clinical trial program; therefore, no evidence of direct or primary cardiac or cardiovascular toxicity was found. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 However, there is no evidence of cardiac dysfunction from afatinib clinical trials to date, and there were no heart failure AEs reported in patients with ERBB2 mutation-positive NSCLC treated with afatinib in this NPU program. 36 The NPU program provides a large pool of patients who have received afatinib in "real life" conditions in clinical practice. However, missing information is an inherent limitation in this type of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the HER2 receptor raised concerns about the cardiological safety of afatinib. Analysis of data from clinical studies, LUX-Lung 3 (229 patients treated with afatinib), LUX-Lung 1 (390 patients treated with afatinib) and 49 other studies (3865 patients treated with afatinib), was designed to determine the risk of heart failure [44]. It appeared that the occurrence of events in clinical randomized studies for 100 patient-years (events/100 patient-years) was similar for afatinib and a placebo (2.40 vs. 2.23), as well as for afatinib and chemotherapy (2.28 vs. 2.92); similar frequency was seen in other studies without randomization (2.88).…”
Section: Afatinibmentioning
confidence: 99%